Optimalisasi Administrasi Guru PAI dalam Meningkatkan Efektivitas Kegiatan Belajar Mengajar di Sekolah - Meti Fatimah; Muhammad Ilyas (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
Abstract Teacher administration is an important component in supporting the effectiveness of teaching and learning activities (KBM), especially in Islamic Religious Education (PAI) subjects. This study aims to examine how optimizing PAI teacher administration can improve the quality of the learning process in schools. The administration in question includes the preparation of learning tools such as syllabus, lesson plans, annual and semester programs, teaching journals, and assessment documents. Through a descriptive qualitative approach, data were obtained from interviews, observations, and documentation of PAI teachers and school management elements. The results of the study show that teachers who manage administration in an orderly and systematic manner tend to be more prepared in delivering material, using appropriate methods, and being able to evaluate student learning outcomes objectively. Optimizing administration not only supports teacher professionalism, but also has an impact on increasing student involvement, efficiency of learning time, and achieving maximum learning objectives. Therefore, support from the school through training, supervision, and provision of digital facilities is very important in encouraging sustainable PAI teacher administration skills. Abstrak Administrasi guru merupakan komponen penting dalam menunjang efektivitas kegiatan belajar mengajar (KBM), khususnya dalam mata pelajaran Pendidikan Agama Islam (PAI). Penelitian ini bertujuan untuk mengkaji bagaimana optimalisasi administrasi guru PAI dapat meningkatkan kualitas proses pembelajaran di sekolah. Administrasi yang dimaksud meliputi penyusunan perangkat pembelajaran seperti silabus, RPP, program tahunan dan semester, jurnal mengajar, serta dokumen penilaian. Melalui pendekatan kualitatif deskriptif, data diperoleh dari wawancara, observasi, dan dokumentasi terhadap guru PAI dan unsur manajemen sekolah. Hasil penelitian menunjukkan bahwa guru yang mengelola administrasi secara tertib dan sistematis cenderung lebih siap dalam menyampaikan materi, menggunakan metode yang tepat, serta mampu mengevaluasi hasil belajar siswa secara objektif. Optimalisasi administrasi tidak hanya mendukung profesionalisme guru, tetapi juga berdampak pada meningkatnya keterlibatan siswa, efisiensi waktu belajar, dan tercapainya tujuan pembelajaran secara maksimal. Oleh karena itu, dukungan dari pihak sekolah melalui pelatihan, supervisi, dan penyediaan sarana digital sangat penting dalam mendorong keterampilan administrasi guru PAI yang berkelanjutan.